The Sub-Analysis of HFmrEF and HFrEF Group in CORE-HF Registry : When being Good is Not Enough - Wasyanto, Trisulo; Irnizarifka, Irnizarifka; Chau, Titus H.; Arifianto, Habibie (The Indonesian Heart Association, 2025)
In “The Sub-Analysis of HFmrEF and HFrEF Group in CORE-HF Registry: When being Good is Not Enough” (Indonesian Journal of Cardiology, 44(1), 10-6. https://doi.org/10.30701/ijc.1545), there is an error noted. An error has been found in the PDF version of this article. The DOI printed in the PDF is incorrect. The correct DOI is https://doi.org/10.30701/ijc.1545. The error occurs only in the PDF; the DOI listed in the article metadata is already correct. The publisher apologizes for any inconvenience caused by this error.DOI of original article: https://doi.org/10.30701/ijc.1545